Spatial Analysis of Relationship Between Teleconnection Patterns and Monthly Temperature of Northwest of Iran - Dr.Mahmood Khosravi; Ebrahim Mesgari (جغرافیا و آمایش شهری منطقه‌ای, 2016)
The purpose of this paper is determining the relationships between teleconnection patterns and temperature in Northwest of Iran. The relationship between 17 teleconnection patterns and Monthly temperature of 24 stations in Northwestern Iran by using Pearson correlation analysis and Stepwise Regression Model during the statistical period of 1992-2011, were used for measuring the relations. Finally, the spatial distribution of the correlation between these patterns and temperature of stations in the study area was drawn and its zoning was prepared by use of Kriging method in GIS environment . The results showed that there is a significant correlation between teleconnection patterns and temperature of the region. So that AO, EP/NP, SOI, MEI and EA/WR patterns have the strongest correlation with the temperature of region and were identified as the most influential patterns. According to lag correlation calculations that were done on lag time of one month, two months and three months, the more significant correlation is the lag time of one month. The strongest significant correlation is related to Sardasht station and EA/WR teleconnection pattern with Correlation coefficient -0.771 in February.